Erythropoietin-Derived Peptide Protects Against Acute Lung Injury After Rat Traumatic Brain Injury - Yuan Liu; Junyu Lu; Xiaoya Wang; Liu Chen; Su Liu; Zhiren Zhang; Wei Yao (Cellular Physiology and Biochemistry, 2017)
Background: Traumatic brain injury (TBI) can be complicated by TBI-triggered acute lung injury (ALI), in which inflammation plays a central role. It has been reported that an Erythropoietin-derived peptide (pHBSP) was able to ameliorate TBI; however, its function in TBI-caused ALI has not been reported yet. Methods: In this study, we studied the effect of pHBSP on TBI-caused ALI by using a weight-drop induced TBI model. At 8 h and 24 h post-TBI, pulmonary edema (PE) and bronchoalveolar lavage fluid (BALF) proteins were measured, and haematoxylin and eosin (H&E) staining of lung sections was carried out. At 24 h following TBI, the lungs were harvested for immunofluorescence staining and qRT-PCR analysis. Results: At 8 h and 24 h post-TBI, pHBSP treatment significantly decreased wet/dry ratios, decreased total BALF protein, and attenuated the histological signs of pulmonary injury. At 24 h post-TBI, pHBSP treatment decreased the accumulation of CD68+ macrophages in the lung and reduced the mRNA levels of TNF-α, IL-6, IL-1β and iNOS in the lung. Conclusions: We identified the protective role that pHBSP played in TBI-caused ALI, suggesting that pHBSP is a potent candidate for systemic therapy in TBI patients.